A New Embedded Analysis with Pinwise Discontinuity Factors for Pin Power Reconstruction. (3rd July 2021) - Yu, Hwanyeal; Jang, Seongdong; Kim, Yonghee
Abstract: Based on embedded analysis, an accurate pin power reconstruction (PPR) method is proposed for conventional nodal analysis. Unlike the common form function (FF) method, the new PPR method, named the embedded pin power reconstruction (EPPR) method, directly solves a two-group fixed-source problem that is defined with pinwise homogenized group constants (HGCs) and coarse-mesh incoming partial currents on the boundary. In the EPPR scheme, the pinwise HGCs including the pinwise discontinuity factor are predetermined from single-assembly lattice calculations, and the boundary partial currents are obtained from two-step nodal analyses. Two EPPR approaches are proposed: One is a 3×3 extended color-set configuration, and the other is a smaller one considering the half-thickness of the surrounding fuel assemblies. The performance of the EPPR methods is evaluated with various benchmark problems including partially mixed oxide–loaded pressurized water reactor cores, and the results are compared with the conventional FF method. Comprehensive results of this work demonstrate that the new EPPR method can provide much better accuracy than the conventional FF-based PPR method.